Propagation of the Vanda helvola Orchid In Vitro - Muharyati, Yully; Setiyadi, Muhammad Wahyu; Khatimah, Ainul; Ardiansyah, Ardiansyah (Jurnal Pijar Mipa, 2024)
Orchids are more economical and tall than plants and other decorations. One of the orchids cultivated is the Vanda orchid. Seed orchid size is small and does not have endosperm, so it is not easy to germinate in nature, so tissue culture is one multiplication orchid in amount a lot and a short time. This study aims to know the growth of the seed orchid Vanda helvola on different media for 12 days after plant. Seed orchid V. helvola grown on modified Murashinge and Shoog (MS), modified Vaccin and Wend (VW) media and organic media. The research was conducted at the Tissue Culture Laboratory of the UPT Center for Food Crops and Horticulture (BBIPTH), Luwus Tanaban, from February to May 2023. The research method used was observation and experimentation, and the research design used RAK (group random design). Research shows modified MS Media, modified VW and organic capable change seeds orchid V. helvola. Modified MS and modified VW media can induce seed orchid V. helvola germination, and MS media can induce formation protocol.